Implementation of Edge Computing IoT-based Database Management System for Renewable Energy Management in Indonesia - Widyatmoko Widyatmoko; Salfin Salfin; Nanny Mayasari; Hanifah Nurul Muthmainah (West Science Information System and Technology, 2023)
The implementation of an IoT Smart Computing-based Database Management System (DBMS) for renewable energy management in Indonesia represents a pivotal step toward sustainable energy practices. This research conducted a comprehensive analysis using both descriptive and inferential statistics based on data collected from 100 renewable energy sources. The results revealed a mean energy production of 500 kWh, coupled with a high mean reliability index of 0.92, indicating a stable and consistent energy supply. Regression analysis highlighted a positive correlation between sunlight exposure and energy production, emphasizing the need for adaptive strategies in harnessing varying climatic conditions. Hypothesis testing confirmed the significant improvement in energy management metrics compared to traditional systems (p < 0.001). The findings provide valuable insights for optimizing renewable energy utilization and offer practical recommendations for stakeholders involved in Indonesia's renewable energy landscape.